Eye Lens Radiation Dose to Nurses during Cardiac Interventional Radiology: An Initial Study - Ayumi Yamada; Yoshihiro Haga; Masahiro Sota; Mitsuya Abe; Yuji Kaga; Yohei Inaba; Masatoshi Suzuki; Norio Tada; Masayuki Zuguchi; Koichi Chida (Diagnostics, 2023)
Although interventional radiology (IVR) is preferred over surgical procedures because it is less invasive, it results in increased radiation exposure due to long fluoroscopy times and the need for frequent imaging. Nurses engaged in cardiac IVR receive the highest lens radiation doses among medical workers, after physicians. Hence, it is important to measure the lens exposure of IVR nurses accurately. Very few studies have evaluated IVR nurse lens doses using direct dosimeters. This study was conducted using direct eye dosimeters to determine the occupational eye dose of nurses engaged in cardiac IVR, and to identify simple and accurate methods to evaluate the lens dose received by nurses. Over 6 months, in a catheterization laboratory, we measured the occupational dose to the eyes (3 mm dose equivalent) and neck (0.07 mm dose equivalent) of nurses on the right and left sides. We investigated the relationship between lens and neck doses, and found a significant correlation. Hence, it may be possible to estimate the lens dose from the neck badge dose. We also evaluated the appropriate position (left or right) of eye dosimeters for IVR nurses. Although there was little difference between the mean doses to the right and left eyes, that to the right eye was slightly higher. In addition, we investigated whether it is possible to estimate doses received by IVR nurses from patient dose parameters. There were significant correlations between the measured doses to the neck and lens, and the patient dose parameters (fluoroscopy time and air kerma), implying that these parameters could be used to estimate the lens dose. However, it may be difficult to determine the lens dose of IVR nurses accurately from neck badges or patient dose parameters because of variation in the behaviors of nurses and the procedure type. Therefore, neck doses and patient dose parameters do not correlate well with the radiation eye doses of individual IVR nurses measured by personal eye dosimeters. For IVR nurses with higher eye doses, more accurate measurement of the radiation doses is required. We recommend that a lens dosimeter be worn near the eyes to measure the lens dose to IVR nurses accurately, especially those exposed to relatively high doses.